Comparing antiretroviral treatment outcomes between a prospective community-based and hospital-based cohort of HIV patients in rural Uganda - Alibhai Arif; Okech-Ojony Joa; Rubaale Tom; Konde-Lule Joseph; Kipp Walter; Saunders Duncan L (BMC, 2011)
Abstract Background Improved availability of antiretroviral therapy in sub-Saharan Africa is intended to benefit all eligible HIV-infected patients; however in reality antiretroviral services are mainly offered in urban hospitals. Poor rural patients have difficulty accessing the drugs, making the provision of antiretroviral therapy inequitable. Initial tests of community-based treatment programs in Uganda suggest that home-based treatment of HIV/AIDS may equal hospital-based treatment; however the literature reveals limited experiences with such programs. The research This intervention study aimed to; 1) assess the effectiveness of a rural community-based ART program in a subcounty (Rwimi) of Uganda; and 2) compare treatment outcomes and mortality in a rural community-based antiretroviral therapy program with a well-established hospital-based program. Ethics approvals were obtained in Canada and Uganda. Results and outcomes Successful treatment outcomes after two years in both the community and hospital cohorts were high. All-cause mortality was similar in both cohorts. However, community-based patients were more likely to achieve viral suppression and had good adherence to treatment. The community-based program was slightly more cost-effective. Per capita costs in both settings were unsustainable, representing more than Uganda's Primary Health Care Services current expenditures per person per year for all health services. The unpaid community volunteers showed high participation and low attrition rates for the two years that this program was evaluated. Challenges and successes Key successes of this study include the demonstration that antiretroviral therapy can be provided in a rural setting, the creation of a research infrastructure and culture within Kabarole's health system, and the establishment of a research collaboration capable of enriching the global health graduate program at the University of Alberta. Challenging questions about the long-term feasibility and sustainability of a community-based ARV program in Uganda still remain. The partnership This project is a continuation of previous successful collaborations between the School of Public Health of Makerere University, the School of Public Health of University of Alberta, the Kabarole District Administration and the Kabarole Research and Resource Center.